The prevalence of antibiotic-resistant and multidrug-resistant bacteria in urine cultures from inpatients with spinal cord injuries and disorders: an 8-year, single-center study - Šámal, Vladimír; Paldus, Vít; Fáčková, Daniela; Mečl, Jan; Šrám, Jaroslav (BMC infectious diseases, 2022)
BACKGROUND: Patients, especially inpatients, with spinal cord lesions and disorders (SCI/D) have an elevated risk of recurrent urinary tract infections with multidrug resistant (MDR) bacteria. This study evaluated antimicrobial resistance and the prevalence of multidrug resistance and determined the risk factors for multidrug resistance. METHODS: In this retrospective cohort study, urine culture results were used to calculate the antimicrobial resistance rate and the incidence of infection with MDR bacteria in the SCI/D population. MDR was defined as acquired nonsusceptibility to at least one agent from three or more antimicrobial categories. The cohort included 402 inpatients from 2013 to 2020, with 1385 urine isolates. We included only the first isolate; duplicate isolates, defined as positive cultures of the same strain within 14 days, were excluded from the evaluation. RESULTS: The most common MDR strains were Klebsiella spp. (29%) and Escherichia coli (24%). MDR isolates were detected in 50% of the samples and extended spectrum beta-lactamase (ESBL)-producing isolates were detected in 26%, while carbapenem resistance was found in 0.1%. Significantly higher rates of infection with MDR bacteria were identified in groups of patients with indwelling urethral/suprapubic catheters (p = 0.003) and severity scores of C1-C4/AIS A-C (p = 0.01). We identified age (OR: 0.99, 95% CI; 0.98-0.99, p = 0.000), sex (OR: 1.55, 95% CI; 1.16-2.06, p = 0.003), management with urethral/suprapubic catheters (OR: 2.76, 95% CI; 2.04-3.74, p = 0.000), and spontaneous voiding (OR: 1.84, 95% CI; 1.03-3.29, p = 0.038) as independent predictors of multidrug resistance in our study population. CONCLUSIONS: We identified a high antibiotic resistance rate and an increasing prevalence of infection with MDR bacteria in the SCI/D inpatient population. Particular attention should be given to bladder management, with an emphasis on minimizing the use of indwelling catheters.
Keywords: poranění míchy; Prevalence; Anti-Bacterial Agents; Retrospective Studies; Neurogenic lower urinary tract dysfunction; ESBL resistance; Neurogenic bladder; prevalence; Spinal cord injury; Microbial Sensitivity Tests; Escherichia coli; Inpatients; Urinary tract infection; retrospektivní studie; Humans; beta-laktamasy; Drug Resistance, Multiple, Bacterial; antibakteriální látky; beta-Lactamases; hospitalizovaní pacienti; mnohočetná bakteriální léková rezistence; mikrobiální testy citlivosti; Spinal Cord Injuries; Multidrug resistance; lidé